2009
DOI: 10.1007/s11010-009-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase receptor expression involves tyrosine phosphorylation of phosphoglycerate kinase

Abstract: The interaction of urokinase-type plasminogen activator (uPA) with its receptor, uPAR, plays a central role in several pathophysiological processes, including cancer. uPA induces its own cell surface receptor expression through stabilization of uPAR mRNA. The mechanism involves binding of a 51 nt uPAR mRNA coding sequence with phosphoglycerate kinase (PGK) to down regulate cell surface uPAR expression. Tyrosine phosphorylation of PGK mediated by uPA treatment enhances uPAR mRNA stabilization. In contrast, inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The degradation of the extracellular matrix requires the involvement of a variety of extracellular proteolytic enzymes, with which the urokinase-type plasminogen activator (uPA) and its receptor (uPAR) play important roles [13]. uPA interacts with uPAR at the tumor cell surface, with uPA concentrated on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of the extracellular matrix requires the involvement of a variety of extracellular proteolytic enzymes, with which the urokinase-type plasminogen activator (uPA) and its receptor (uPAR) play important roles [13]. uPA interacts with uPAR at the tumor cell surface, with uPA concentrated on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also demonstrated that tyrosine phosphorylation of PGK enhances uPAR mRNA stabilization, thereby stimulating receptor synthesis [40]. To date, no evidence is available about the effect of Y76 phosphorylation on the enzyme activity but mutational studies revealed that inhibition of tyrosine phosphorylation increases PGK binding to uPAR mRNA and attenuates uPA-induced uPAR expression [40]. Interestingly, it has been shown that, upon overexpression, uPAR assembles with and activates α5β1-integrin and EGFR, thereby favouring the activation of PI3K/ pAKT/mTOR/HIF-1α signaling pathway [41].…”
Section: Phosphoglycerate Kinase (Pgk)mentioning
confidence: 97%
“…Shetty and co-authors reported that the binding of urokinase-type plasminogen activator (uPA) to its receptor (uPAR) promotes phosphorylation of the Y76 residue of PGK. Moreover, they also demonstrated that tyrosine phosphorylation of PGK enhances uPAR mRNA stabilization, thereby stimulating receptor synthesis [40]. To date, no evidence is available about the effect of Y76 phosphorylation on the enzyme activity but mutational studies revealed that inhibition of tyrosine phosphorylation increases PGK binding to uPAR mRNA and attenuates uPA-induced uPAR expression [40].…”
Section: Phosphoglycerate Kinase (Pgk)mentioning
confidence: 99%
“…In the case of the human phosphoglycerate kinase 1 (PGK1), a glycolytic enzyme that moonlights during tumour angiogenesis [35], early studies showed that it can bind the mRNA of the urokinase plasminogen activator surface receptor (PLAUR) and regulate its expression. This is mediated by the phosphorylation of a PGK1 tyrosine residue (Y76), that reduces the binding affinity of PGK1 to PLAUR mRNA, resulting in its stabilization and expression induction [36].…”
Section: Involvement Of Short Linear Motifs In Functional Changesmentioning
confidence: 99%